Effect of Self- and Inter-Cultivar Grafting on Growth and Nutrient Content in Sweet Basil (Ocimum basilicum L.) - Hollick, Jason R.; Kubota, Chieri (Frontiers in Plant Science, 2022)
Vegetable grafting has been applied to fruiting crops, yet only to a limited extent in leafy greens and herbs which may also benefit from grafting. In this study we examined the effect of reciprocal grafting two sweet basil (Ocimum basilicum L.) cultivars of differing vigor on plant growth and leaf mineral nutrient concentration to test whether differences in growth exist due to grafting and whether such differences are due to altered plant nutrient status in two trials. Two cultivars ‘Nufar’ (NU), a high vigor cultivar, and ‘Dolce Fresca’ (DF), a cultivar developed for compact growth, were selected. Four grafted treatments (scion/rootstock) were created by self-grafting (NU/NU and DF/DF) and reciprocal inter-cultivar grafting (DF/NU and NU/DF). Un-grafted plants (ug-NU and ug-DF) served as controls. Following grafting, plants were grown for 26 or 21 days in a greenhouse. DF rootstocks decreased NU shoot dry mass (19-29%) and stem length (12%) compared to ug-NU in both trials, while dry root mass was reduced (28%) in the second trial. In contrast, NU rootstocks did not affect DF growth in the first trial but significantly decreased dry shoot (18%) and root (31%) mass, compared to ug-DF in the second. Concentration of most inorganic nutrients examined were affected by both rootstock and scion genotype. For NU scions, DF rootstocks resulted in significantly higher (5-29%) levels of nitrogen, phosphorus, potassium, calcium, magnesium, sulfur, copper, and zinc in leaf tissue than ug-NU. For DF scions, NU rootstocks resulted in significantly higher (7-9%) levels of potassium and phosphorus but significantly lower (11-23%) levels of magnesium, sulfur, boron, copper, and zinc when compared to ug-DF. Results of this study show that inter-cultivar grafting sweet basil using a more vigorous cultivar as a rootstock did not enhance the growth of a less vigorous scion and reduced concentrations of certain nutrients. However, grafting a vigorous scion to a less vigorous rootstock reduced shoot growth but generally increased nutrient concentrations. This suggests that changes in growth in grafted basil is not due to altered nutrient status. Further research is needed to determine specific physiological processes influencing grafted basil growth.